2021
DOI: 10.1101/2021.10.04.463061
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sweet revenge: AtSWEET12 in plant defense against bacterial pathogens by apoplastic sucrose limitation

Abstract: Depriving bacterial pathogens of sugars is a potential plant defense strategy. The relevance of SUGARS WILL EVENTUALLY BE EXPORTED TRANSPORTERS (SWEETs) in plant susceptibility to pathogens has been established, but their role in plant defense remains unknown. We identified Arabidopsis thaliana SWEETs (AtSWEETs) involved in defense against nonhost and host Pseudomonas syringae pathogens through reverse genetic screening of atsweet1-17 mutants. Double/triple mutant, complementation, and overexpression line anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 47 publications
1
12
0
Order By: Relevance
“…It has been reported that OsSWEET12 (Li et al 2013 ) and AtSWEET11 (Wipf et al 2021 ) interact with AtRBOHD, a membrane NADP oxidase producing reactive oxygen species involved in defence-related processes. In line with the present interpretation, SWEETs were proposed to modulate the sucrose availability for pathogens (Fatima and Senthil-Kumar 2021 ).…”
Section: Discussionsupporting
confidence: 79%
“…It has been reported that OsSWEET12 (Li et al 2013 ) and AtSWEET11 (Wipf et al 2021 ) interact with AtRBOHD, a membrane NADP oxidase producing reactive oxygen species involved in defence-related processes. In line with the present interpretation, SWEETs were proposed to modulate the sucrose availability for pathogens (Fatima and Senthil-Kumar 2021 ).…”
Section: Discussionsupporting
confidence: 79%
“…The study traced the AtSWEET11-mediated sucrose flux to be modulated through AtSWEET12 via plasma membrane targeting and an oligomerization-dependent regulatory mechanism in Arabidopsis. This also indicates the exclusive role of AtSWEET12 in suppressing bacterial multiplication and the role of AtSWEET11 in supplying sugars to bacterial pathogens in the apoplast (Fatima and Senthil-Kumar, 2021).…”
Section: Resultsmentioning
confidence: 94%
“…It is highly plausible that these transporters are independently regulated through PTM at the CTD, which might be a reason for distinct and exclusive roles of these two transporters in various plant physiological processes. Although, the phenotypic analysis for the double mutant of AtSWEET11 and AtSWEET12 points towards the functional redundancy (Chen et al, 2012; Gebauer et al, 2016; Walerowski et al, 2018), the histochemical and expression-based studies of the single mutants of these two transporters demonstrate their distinct roles in various developmental processes (Chen et al, 2015; Le Hir et al, 2015), as well as in response to environmental stimuli (Fatima and Senthil-Kumar, 2021). The differential expression of AtSWEET11 and AtSWEET12 orthologs also support their specific roles in different plant species ( Supplementary Figure 8 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study traced the AtSWEET11‐mediated sucrose flux to be modulated through AtSWEET12 via plasma membrane targeting and an oligomerization‐dependent regulatory mechanism in Arabidopsis. This also indicates the exclusive role of AtSWEET12 in suppressing bacterial multiplication and the role of AtSWEET11 in supplying sugars to bacterial pathogens in the apoplast (Fatima & Senthil‐Kumar, 2021). In the present study, a large number of cis‐acting elements related to defense and biotic stress, such as MYB and MYC elements were abundantly distributed in the promoter sequences of AtSWEET11 and AtSWEET12 orthologs from different plant species, followed by STRE, ARE, LTR, W box, WUN, and MBS elements (Figure 4).…”
Section: Discussionmentioning
confidence: 97%